Dialectic and Intersection of Sufism and Kalam in the First and Second Centuries of Hijri - Yogi Prana Izza (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2020)
This article seeks to examine the dialectic of Sufism orientation and Kalam with a special focus on the intersection between these two realms during the First and Second Hijri centuries. Consequently, three aspects, which are the background and chronology of the intersection, the issues that arose in it, as well as the associated characteristics, were emphasized. The study revealed that the political, sociological, intellectual, and academic factors became the background of the intersection between Sufism and Kalam in the First and Second Hijri centuries. Also, the main issues developed were faith or īmān, infidelity, or kufr, and the problems of human deeds, known as af‘āl al-‘ibād. Other issues were the relationship of the essence or dhāt, as well as the divine attributes or ṣifāt of Allah. Meanwhile, the three characteristics of the intersection that were mapped were, first, the interrelation of doctrine and political attitudes. This interrelation means that a strong correlation, or even integration, exists between the doctrine of a sect, known as firqah, and political attitudes. Second, a thematic theological interconnection signified that there were common issues discussed in matters of theology. Third, a rational debate based on rational approaches indicated that the conflict of thoughts that occurred was essentially a dialogue as it was not on a different study line but in the same area.